PELATIHAN VIRTUAL PEMERIKSAAN PAP SMEAR - Marlin Margareth Maelissa; Hadilah Rahawarin; Nathalie Elischeva Kailola; Vina Zakiah latuconsina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2021)
Early detection through a screening program is one of the strategy to prevent cervical cancer that can help reduce cervical cancer morbidity and mortality. One of the method of early detection is through a pap smear evaluation. This workshop was held with the aim of increasing the knowledge of health workers, especially midwives, about pap smear evaluation. The activity was carried out online with a duration of five hours, the topics include Gynecological Procedures in the Pandemic Era of COVID19, Anatomy of the Female Reproductive System, Cervical Cancer and Pap smear Cytology presented by gynecologist and pathologist, followed by video streaming of cervical specimen collection methods for pap examination smear. Participants consisted of midwives as the main target, general practitioners, nurses, preclinical and clinical medical students, and midwifery students. The activity went well and smoothly, accompanied by discussions and sharing experiences about cervical cancer prevention services. There was an increase in knowledge from 39.42% to 68.33%. It is hoped that the knowledge gained from this activity can be applied in the services of health workers in their respective work areas so that it can help improve women's reproductive health and cervical cancer prevention.